A Comparison of Two Methods Using R.M.S. Value and Wavelet-Based Mann and Morrison Algorithm for Voltage Dip Characterization - Abd Halim, Syahirah (Universiti Teknologi Petronas, 2009)
Voltage dips have been identified as the major problem among power quality disturbance events which affect the industrial customers. The dips involve short reduction in Root Mean Square (RMS) voltage caused by fuults in electrical supply system or starting of a large load. It is crucial to measure and analyze the voltage dip events before considering any mitigation action to reduce and eliminate it. This work presents comparison of two methods used for voltage dip detection and characterization. A less complicated method performed is to determine the lowest magnitude of the RMS voltage during the disturbance. Another method is a combination of wavelet-based analysis using Mann and Morrison algorithm which estimates the amplitude and the phase angle to characterize the dips. The performances of both methods are examined using simulation of system voltage dip, duration of the dip occurrences and point-on wave at beginning in a sinusoidal voltage supply. The voltage dips are then being classified into some classes according to their characteristics. The numerical approach using RMS value results in simplicity method which is easy to be implemented and understood. Eventhough the wavelet-based method seems to be more complicated, it provides higher accuracy in determining the voltage dip characterization. iii